(untitled) (Academicia Globe: Inderscience Research, 2022)
The article presents the results of scientific research work carried out to optimize the water and salt procedures of the soil with the help of phytomeliatory measures in the conditions of medium-loamy, moderately saline soils, according to the alluvial, mechanical composition of the meadow of the Bukhara region, to economy the river waters, which are spent on watering agricultural crops and washing